2009
DOI: 10.1128/jvi.00557-09
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to the Buried N Terminus of Rhinovirus VP4 Exhibit Cross-Serotypic Neutralization

Abstract: Development of a vaccine for the common cold has been thwarted by the fact that there are more than 100 serotypes of human rhinovirus (HRV). We previously demonstrated that the HRV14 capsid is dynamic and transiently displays the buried N termini of viral protein 1 (VP1) and VP4. Here, further evidence for this "breathing" phenomenon is presented, using antibodies to several peptides representing the N terminus of VP4. The antibodies form stable complexes with intact HRV14 virions and neutralize infectivity. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 31 publications
9
79
1
Order By: Relevance
“…These structural changes lead to the formation of roughly rectangular (25 Å × 8 Å) pores around the icosahedral twofold axes through which the viral RNA and VP4 might exit (Figs. 1 and 2) (24,25). In addition, because of the rigid body movements and the disordering of residues 3172-3181 in the VP3 GH loop (the loop that links β-strands G and H), pores are opened up near the quasi-threefold axes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These structural changes lead to the formation of roughly rectangular (25 Å × 8 Å) pores around the icosahedral twofold axes through which the viral RNA and VP4 might exit (Figs. 1 and 2) (24,25). In addition, because of the rigid body movements and the disordering of residues 3172-3181 in the VP3 GH loop (the loop that links β-strands G and H), pores are opened up near the quasi-threefold axes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most antibodies generated to RV infection in humans are directed against epitopes found on surface-exposed structures of VP1, VP2 and VP3 (Carey et al, 1992). Although there is evidence that the N-terminus of VP4 may be transiently exposed at the capsid surface in a process known as capsid breathing (Lewis et al, 1998) and antibodies to this region of VP4 are cross-serotype protective (Katpally et al, 2009), naturally occurring human antibodies to VP4 have not been described. A recent study by Niespodziana et al revealed that children with RV-induced respiratory symptoms primarily generate IgG1 and IgA to N-terminal regions of VP1 and that responses to VP2, VP3 and VP4 were significantly lower .…”
Section: Discussionmentioning
confidence: 99%
“…These residues at the N-terminal of VP1, which have similar polar, hydroxyl-group containing side chains, are located in the internal surface of the capsid in close proximity to the N-terminal of VP2 and VP4. Neutralizing antibodies to the internal epitopes of VP1 and VP4 have been reported in poliovirus and rhinovirus (Katpally et al, 2009;Li et al, 1994;Roivainen et al, 1993). However, neutralizing antibodies to internally located epitopes of FMDV have not been reported.…”
Section: Discussionmentioning
confidence: 99%